2022
DOI: 10.1038/s41419-022-04833-6
|View full text |Cite
|
Sign up to set email alerts
|

HJURP regulates cell proliferation and chemo-resistance via YAP1/NDRG1 transcriptional axis in triple-negative breast cancer

Abstract: Triple-negative breast cancer is still a difficult point in clinical treatment at present, and a deep study of its pathogenesis has great clinical value. Therefore, our research mainly focuses on exploring the progression of triple-negative breast cancer and determines the important role of the HJURP/YAP1/NDRG1 transcriptional regulation axis in triple-negative breast cancer. We observed significantly increased HJURP expression levels in triple-negative breast cancer compared to other subtypes. HJURP could aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Indeed, our study identifies several aspects of HJURP that deserve further study, including the downstream effector molecules that mediate the observed associations between HJURP and HCC pathogenesis. HJURP has already been shown to regulate pathways involving GSK3β/JNK, p53, Wnt/ β-catenin, MDM2/p53, YAP1/NDRG1, MAPK/ERK1/2, AKT/ GSK3β, and SPHK1 (11)(12)(13)(14)(35)(36)(37). Among these pathways, those involving MAPK/ERK1/2 and AKT/GSK3β have been associated with HCC proliferation (13), while SPHK1 signaling has been associated with the epithelial-to-mesenchymal transition in HCC (37).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our study identifies several aspects of HJURP that deserve further study, including the downstream effector molecules that mediate the observed associations between HJURP and HCC pathogenesis. HJURP has already been shown to regulate pathways involving GSK3β/JNK, p53, Wnt/ β-catenin, MDM2/p53, YAP1/NDRG1, MAPK/ERK1/2, AKT/ GSK3β, and SPHK1 (11)(12)(13)(14)(35)(36)(37). Among these pathways, those involving MAPK/ERK1/2 and AKT/GSK3β have been associated with HCC proliferation (13), while SPHK1 signaling has been associated with the epithelial-to-mesenchymal transition in HCC (37).…”
Section: Discussionmentioning
confidence: 99%
“…We also noticed this inconsistency in HJURP sub-localization in previous studies. In hepatocellular carcinoma, prostate cancer, ovarian cancer, and breast cancer, IHC showed that HJURP was mainly expressed in cell cytoplasm ( 16 , 21 24 ); nevertheless, HJURP was mainly observed in cytoplasm in pancreatic cancer and colorectal cancer ( 15 , 17 ). The underlying mechanism of this expression phenotype is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously inhibiting YAP activity can improve the therapeutic effect of liver cancer patients with drug resistance mechanism [45] . In breast cancer, YAP1 also can affect chemotherapy sensitivity through the HJURP/YAP1/NDRG1 axis [46] . However, there is still no research on the drug resistance mechanism of YAP1 in LCNEC, so the underlying mechanism of drug resistance induced by YAP1 still remains obscure.…”
Section: Discussionmentioning
confidence: 99%